How Technology Adoption and Trade Are Shaping Indonesian Labor Markets - Viollaz, Mariana (2019)
This paper analyzes the simultaneous impacts and interplay of exports and technology adoption on the demand for different types of skills and aggregate labor market indicators in Indonesia over a period characterized by a commodity boom (2005-10) and a period of declining exports (2011-15). The results for the 2005-10 sub-period are in line with the evidence available for developed countries, that is, technology is complementary to analytical and soft skills and is labor-saving, while exports are labor increasing. In 2011-15, the relationship between technology and skills, and between technology and labor demand, differs from the evidence available for the developed world. That is, technology increases the demand for analytical and interpersonal skills in high-exporting industries only, and technology and exports are labor increasing for some population subgroups. The findings for the more recent period confirm that differences in economic structures matter for understanding the impacts of technological advances and globalization.